Gastric bezoar: a simple and innovative lithotripsy method—a case report and review of the literature - Yan, Xudong (Frontiers in Gastroenterology, 2025)
Gastrointestinal bezoars result from the ingestion of indigestible materials and are classified by their consistency. This material is commonly located in the stomach. Human bezoars may be formed by non-digestible plant fibers (phytobezoars), persimmons (diospyrobezoar), hair (trichobezoar), long-acting medications (pharmacobezoar), milk and mucus components (lactobezoar), or other various substances. This condition may be asymptomatic, or it may cause symptoms such as stomachache, ulcers, bleeding, perforation, gastric outlet obstruction, and mechanical intestinal obstruction. We herein report a simple and innovative lithotripsy method using Zebra Guidewire, and review the pathogenesis, clinical manifestations, and treatment of bezoars.